180-W XPS GreenLight laser vaporization for benign prostate hyperplasia: 12-month safety and efficacy results for glands larger than 80 ml - Altay, Bülent; Erkurt, Bülent; Kiremit, Murat Can; Güzelburç, Vahit; Boz, Mustafa Yücel; Albayrak, Selami (Springer London, 2015)
The purpose of the current study was to evaluate the efficacy and safety of laser prostatectomy by using the latest 180-W XPS GreenLight laser with the new MoXy fiber in the surgical treatment of glands larger than 80 mL in a prospective study. From December 2011 to May 2013, 68 consecutive patients with a mean age of 71.1 +/- 9.8 years (range 49 to 85) underwent 180-W XPS laser prostatectomy at our institution. The baseline characteristics, perioperative data, and complications were recorded. Evaluation of outcomes was assessed at 3, 6, and 12 months postoperatively comparing subjective (International Prostate Symptom Score [IPSS], International Index of Erectile Function-5 [IIEF-5]) and objective (Maximal flow rate [Q(max)], postvoid residual urine [PVR], transrectal ultrasound [TRUS] volume) parameters to the preoperative data. Mean preoperative prostate volume was 104.3 +/- 29.7 mL (range 81 to 185). Mean operation time was 65.5 +/- 29.6 min (range 38 to 124), with a mean energy delivery of 398 +/- 169 kJ (range 39 to 523). The catheterization time was 20.8 +/- 1.9 h (range 6 to 92) and the hospital stay was 27.3 +/- 8.7 h (range 12 to 80). No major intraoperative complications were observed. Improvement in IPSS, Q(max), and PVR was statistically significant (p < 0.001) at 3, 6, and 12 months. Urethral strictures were observed in two patients (2.9 %). No patients required reintervention due to residual adenoma. The average volume reduction was 40.5 % at 12 months. Photoselective vaporization of the prostate (PVP) using the new 180-W XPS GreenLight laser system seems to be a safe and effective procedure and could play an important role in the surgical treatment of symptomatic benign prostatic hyperplasia (BPH) patients with larger prostate volumes.
WOS: 000348297900042
PubMed ID: 25274195
Keywords: Photoselective Vaporization of Prostate; Benign Prostatic Hyperplasia; GreenLight; Nd:YAG Laser